Hubungan Antara Sikap Disiplin Terhadap Hasil Belajar - Dwi Ria Ibti Disma; Haratua Tiur Maria; Venny Karolina (LP. Ma'arif Janggan Magetan, 2023)
This research aims to determine the relationship between students' disciplinary attitudes and student learning outcomes. The method used in this research is experimental research analysis. This research uses the Pearson correlation (product moment) test. The data collection instrument is through final semester grades with a sample size of 30 people. Based on data testing using the Pearson correlation test, the sig value was obtained. 0.000 < 0.05 which indicates that there is a relationship between students' discipline attitudes and student learning outcomes, and has a degree of relationship of 0.603 which is categorized as a strong relationship. So from this description it can be concluded that there is a significant influence between students' disciplinary attitudes on the informatics learning outcomes of class XF students at SMAN 9 Pontianak and this relationship has a strong status.